Post-operative Outcome during Off-Pump Coronary Artery Bypass Surgery – A Comparison between Combined High Thoracic Epidural Anaesthesia with General Anaesthesia and General Anaesthesia Alone - Azad, Saiful Islam; Alam, Sarif Shammirul; Beg, Abdul Khaleque (Cardiovascular Journal, 2022)
Background: In the postoperative period inadequate analgesia may increase morbidity by causing adverse haemodynamic, metabolic, immunologic and haemostatic attentions and prolong mechanical ventilation with more ICU stay. This study has been undertaken to compare postoperative outcome in off-pump coronary artery bypass surgery (OPCAB) between high thoracic epidural anaesthesia (HTEA) as an adjunct to general anaesthesia (GA) vs. GA alone. Methods : This prospective, randomized case control comparative study was carried out in sixty patients without having left main coronary artery disease, left ventricular ejection fraction <30% or contraindication of regional anaesthesia scheduled for OPCAB. They were divided into two groups, thirty in each group. Group A received GA alone and group B received high thoracic epidural anaesthesia with GA. Requirement of postoperative analgesics, pain score, sedation score, and post-operative complications were evaluated. Results: Rescue analgesics was needed in 16 (53.3%) and 6 (20.0%) patients in group A and group B respectively (p<0.05). Post-operative pain score (VAS) during maintenance with ventilator with awareness at first fourth hour and after extubation during movement & cough were significantly different between two groups. Post-operative sedation score was significantly different between two groups except in 1st hour. No post-operative complication was observed in both groups. Conclusion: High thoracic epidural anaesthesia with GA appeared to be most reliable postoperative pain reliever with better post-operative outcome in OPCAB surgery. Cardiovasc j 2022; 15(1): 63-68